Impact of Local Content Restrictions and Barriers against Foreign Direct Investment in Services : The Case of Kazakhstan's Accession to the World Trade Organization - Jensen, Jesper; Tarr, David (2012)
We employ a computable general equilibrium model of the Kazakh economy to assess the effect of accession to the World Trade Organization (WTO). Our model incorporates foreign direct investment by multinational business service providers and by multinational oil and gas companies; it contains endogenous productivity effects in both goods and services markets through a Dixit-Stiglitz (1977) framework. Our model is innovative in that we assess the effect of local content provisions for multinational oil and gas companies, provisions that are highly contentious in WTO accession negotiations. We show that our model features are crucial to the results, as the estimated gains are more than ten times larger than the gains from a constant return-to-scale model.